2021
DOI: 10.1111/jmwh.13284
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Visits in Prenatal Care: An Integrative Review

Abstract: Introduction Addressing gaps in access to prenatal care is an important step to reversing rising rates of maternal and neonatal morbidity and mortality and invites the exploration of innovative care models. This integrative review of published literature explores the patient, health care provider, and organizational experience of integrating virtual visits in prenatal care. Methods A literature search to identify original studies and quality improvement projects published between 2010 and 2020 was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 37 publications
3
47
0
1
Order By: Relevance
“… 26 33 This result showed that the high satisfaction levels of pregnant women regarding phone clinics are common and have been reported by several studies. 27 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“… 26 33 This result showed that the high satisfaction levels of pregnant women regarding phone clinics are common and have been reported by several studies. 27 …”
Section: Discussionsupporting
confidence: 76%
“… 26 33 Patients indicated the time and cost reductions associated with not requiring to take time off work, organize childcare, or get transportation, consistent in rural and urban settings. 26 33 This result showed that the high satisfaction levels of pregnant women regarding phone clinics are common and have been reported by several studies. 27 …”
Section: Discussionmentioning
confidence: 99%
“…A gap remains, therefore, in understanding the conditions required for safe and acceptable DC-CON implementation and in understanding the factors that underpin variation in experience. For example: variations between women of different ethnicities (to ensure that DC-CON does not further exacerbate racial inequalities in maternity care)51; how women who face communication barriers will be supported by workers to understand their care and make choices via DC-CON16 52–55; and how access to the technologies necessary for DC-CON will vary between service users and service providers as a result of financial resources, internet connectivity, digital literacy and the digital maturity of NHS services 4 52 56. Such variation is problematic, as it is implementation in real-world contexts, at scale, that needs to be understood for the systemwide transformation as envisaged in the NHS Maternity Transformation Programme 2 21 57.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, é interessante utilizar a telemedicina aliada a assistência presencial, principalmente no contexto de complicações na gravidez. Isso é ratificado por outras revisões como a de Montagnoli et al (2021) e Wu et al (2022) que analisam a teleassistência no pré-natal como benéfica, especialmente na conjuntura pandêmica, mas no contexto atual, em modalidade mista, contando com um vínculo presencial é melhor aceita tanto por pacientes como por profissionais.…”
Section: Introductionunclassified